Ability-based evolution promotes cooperation in interdependent graphs. (6th November 2019) - Jia, Danyang; Shen, Chen; Li, Xuelong; Boccaletti, Stefano; Wang, Zhen
Abstract: We study the influence of players' ability in promoting cooperation in a social dilemma game on interdependent networks. Namely, players of a network whose ability exceeds a given threshold are allowed to form additional links with corresponding players on another network. As individual ability is constantly updated, the resulting coupling architecture between the two networks is time-dependent. Our results demonstrate that such an interdependency helps cooperators to survive, and effectively alleviates the social dilemma by adjusting the coupling spontaneously. The coupling structure, and in particular the directionality of link between cooperators, plays a crucial role in this latter process. Finally, we reveal that the individuals' ability follows a power-law distribution whenever the system reaches a heterogeneous stable state, whereas it obeys a uniform distribution when the attained stable state is homogeneous.